Polyamine receptors containing anthracene as fluorescent probes for ketoprofen in H2O/EtOH solution. Issue 50 (1st June 2022) - Romano, Giammarco Maria; Mummolo, Liviana; Savastano, Matteo; Paoli, Paola; Rossi, Patrizia; Prodi, Luca; Bencini, Andrea
Abstract : Triamine-based receptors containing 2 anthracene units are able to signal ketoprofen in H2 O/EtOH solution via fluorescence emission enhancement, exploiting a proton transfer process upon substrate coordination. Abstract : Triamine receptors containing anthracene units are able to bind and sense ketoprofen via fluorescence enhancement in a H2 O/EtOH 50 : 50 (Vol : Vol) mixture exploiting their protonation features, which are tuned by the interaction with the analyte.